Atlas-Based Quantification of DTI Measures in a Typically Developing Pediatric Spinal Cord - Shahrampour, S.; De Leener, B.; Alizadeh, M.; Middleton, D.; Krisa, L.; Flanders, A.E.; Faro, S.H.; Cohen-Adad, J.; Mohamed, F.B. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Multi-parametric MRI, provides a variety of biomarkers sensitive to white matter integrity, However, spinal cord MRI data in pediatrics is rare compared to adults. The purpose of this work was 3-fold: 1) to develop a processing pipeline for atlas-based generation of the typically developing pediatric spinal cord WM tracts, 2) to derive atlas-based normative values of the DTI indices for various WM pathways, and 3) to investigate age-related changes in the obtained normative DTI indices along the extracted tracts.MATERIALS AND METHODS: DTI scans of 30 typically developing subjects (age range, 6–16 years) were acquired on a 3T MR imaging scanner. The data were registered to the PAM50 template in the Spinal Cord Toolbox. Next, the DTI indices for various WM regions were extracted at a single section centered at the C3 vertebral body in all the 30 subjects. Finally, an ANOVA test was performed to examine the effects of the following: 1) laterality, 2) functionality, and 3) age, with DTI-derived indices in 34 extracted WM regions.RESULTS: A postprocessing pipeline was developed and validated to delineate pediatric spinal cord WM tracts. The results of ANOVA on fractional anisotropy values showed no effect for laterality (P = .72) but an effect for functionality (P < .001) when comparing the 30 primary WM labels. There was a significant (P < .05) effect of age and maturity of the left spinothalamic tract on mean diffusivity, radial diffusivity, and axial diffusivity values.CONCLUSIONS: The proposed automated pipeline in this study incorporates unique postprocessing steps followed by template registration and quantification of DTI metrics using atlas-based regions. This method eliminates the need for manual ROI analysis of WM tracts and, therefore, increases the accuracy and speed of the measurements.ADaxial diffusivityCVcoefficient of variationDFdorsal funiculiFAfractional anisotropyLFlateral funiculiMDmean diffusivityRDradial diffusivityVFventral funiculi